Penerapan Mesin Spinner dan Pendampingan Pengemasan Produk Makanan Pothil Di Desa Mejing, Kecamatan Candimulyo Kabupaten Magelang - Rany Puspita Dewi; Trisma Jaya Saputra; Nurhadi, Nurhadi; Sigit Joko Purnomo; Herru Santosa Budiono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
UD Barokah, produces traditional food “pothil”, is located in Mejing Village, Candimulyo District, Magelang Regency, is approximately 7 km from Tidar University. It produces pothil up to 50 kg/day with a selling price of IDR 70,000/kg. The pothil production process, from preparing ingredients to packaging, is still done manually. The processes that are still done manually are the process of draining the oil and the packaging process which still uses large clear plastic about 5 kg. The packaging also did not include a product label. The aim of this activity is to aid the Mejing Village community in the process of preserving and packaging pothil products. Through this assistance, it is hoped that it will be able to increase the sales reach of pothil products to the general public in areas outside the Magelang Regency. The activity was carried out in two stages, the first stage was observation with discussion with partners and the second stage, problem solving by assisting in the process of preserving and packaging pothil products. The output of this activity is to improve the quality and sales capacity of Mejing Village pothil products and expand the marketing reach of pothil products.